Pembuatan Media Pembelajaran Interaktif dan Menarik Menggunakan Wordwall - Sudianto, Sudianto; Wibowo, Rohim Isnain Septian (FKIP Universitas Majalengka, 2024)
The development of technology in the field of education has created opportunities for educators to design more interactive and engaging learning media. One platform that can be utilized is Wordwall, a digital tool that enables teachers to create various types of quizzes, educational games, and other interactive activities. This community service program aims to enhance the skills of prospective mathematics teachers in using Wordwall as an innovative learning medium, thereby increasing student motivation and engagement in the learning process. The implementation methods of this program include training, mentoring, and hands-on practice in designing and applying Wordwall-based learning media. The primary target of this program is prospective mathematics teachers at Universitas Majalengka who seek to develop more dynamic and enjoyable teaching methods. The results of this program indicate that the training participants were able to integrate Wordwall into their teaching, showing a significant improvement in creativity and teaching effectiveness. Moreover, the use of Wordwall has proven to increase students' interest in learning due to its interactive and game-based nature.